Pine savanna plant community disassembly after fire suppression. (29th January 2020) - Diaz‐Toribio, Milton H.; Carr, Susan; Putz, Francis E.
Abstract: Questions: Biodiversity is being lost rapidly due to anthropogenic changes in land use, climate, and other environmental conditions. In fire‐maintained ecosystems, altered fire regimes accelerate native species loss — community disassembly — and promote recruitment of fire‐sensitive species. In this study, we ask whether fire suppression results in changes over time in functional trait composition of ground‐layer species and whether these changes differ in longleaf pine savannas invaded by hardwoods from those invaded by sand pines. Location: Five Floridian locations on the southeastern coastal plain of the United States. Methods: At each location we selected a fire‐maintained and fire‐suppressed savanna and measured percent plant cover by ground‐story species in 1, 000 m 2 plots. For 102 of these species, we measured 10 functional traits — height, growth form, specific leaf area, leaf dry matter content (LDMC), leaf water content, leaf ignition time, leaf mass consumed by fire, light compensation points (LCPs), non‐structural carbohydrate concentrations in under‐ground organs, and seed mass. Results: Fire exclusion was associated with reductions in both functional diversity and species richness. We identified 38 species exclusive to frequently burned sites: these species showed high LDMC values, high LCPs, high leaf mass consumed, and low leaf ignition time values. Lack of fire was associated with loss of 6 of the 12 C4 native grass species. Species and functional trait composition were affected by both time‐since‐fire and whether post‐fire communities were invaded by broadleaved trees ( Quercus spp. and Liquidambar styraciflua ) or by sand pine ( Pinus clausa ). Conclusions: We demonstrated the effects of altered disturbance regimes on savanna plant species and functional trait composition. This trait‐based approach advanced our understanding of how altered disturbance regimes can alter plant communities. Although 38 shade‐intolerant and flammable native savanna species were absent by 10 years since fire, 12 such species persisted even 40 years after fire exclusion. Abstract : We described the community disassembly process in pine savannas after fire suppression. Specifically, we explored the effects of fire‐altered regimes on plant community dynamics. Our results revealed remarkable losses of species after fire suppression that were related to functional traits of the ground‐layer species. Fire suppression and canopy composition interacted to influence community composition of invaded savannas.